Moje Nalewki - Singer, Bernard, 1893-1966. (Warszawa : Czytelnik, 1993)
Memoirs of life in the Warsaw Jewish quarter at the turn of the century.
Keywords: Singer, Bernard, -- 1893-1966.; Jews -- Poland -- Warsaw -- Biography; Warsaw (Poland) -- Social life and customs